Pemakaian Leksikon dalam Tradisi Penjamasan Pusaka Sunan Kalijaga di Kabupaten Demak (Sebuah Kajian Antropolinguistik) - Zulfa, Ilma; Suyanto, Suyanto (Indonesian literature Program, Faculty of Humanities, Diponegoro University, 2022)
Tradisi penjamasan pusaka Sunan Kalijaga contains an interesting lexicon to study. Understanding the meaning of the lexicon is only known to a few speakers. This study aims to determine the lingual form lexical meaning and cultural meaning lexicon in the text tradisi penjamasan pusaka Sunan Kalijaga. The theory used to explain this study is anthropolinguistic theory by Alessandro Duranti. The methods for collecting data are interviews and literature studies. The presentation of the results of data analysis is informal. The results of this study reveals that the lexicon in tradisi penjamasan pusaka Sunan Kalijaga has meaning as prayer, hope and teachings in life. In addition, the lexicon in tradisi penjamasan Pusaka Sunan Kalijaga has the value of the relationship between human and God, the relationship between humans and humans, the relationship between humans and nature and humans with themselves. All of lexicon is the reflection of the people’s culture in Demak Regency.